Usaha Kesehatan Sekolah (UKS) dalam Upaya Pencegahan Penyebaran COVID-19: Health promotion school (HPS) in preventing the spread of COVID-19 - Nunung Siti Sukaesih; Popi Sopiah; Emi Lindayani; Sri Wulan Linda Sari; Hikmat Pramajati; Dewi Dolifah; Shafa Aghniya Tsurayya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The government's efforts to address learning loss concerns as a result of the COVID-19 pandemi on school-age children are with the gradual start of face-to-face learning. UKS is the implementation of Health Promoting School (HPS) in Indonesia which aims to mobilize and improve health campaigns and education, including efforts to prevent the spread of COVID-19. Most of the UKS in West Java province is in a state of disrepair. In fact, UKS is the spearhead of community empowerment in the implementation of PHBS and is also the main key to preventing the spread of COVID-19 in the school environment. The purpose of this community service is to optimize the role of HPS during the COVID-19 pandemi. Community service program method developed by the team based on the modified